2011
DOI: 10.1007/s11427-011-4197-3
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic ADP-ribose and NAADP: fraternal twin messengers for calcium signaling

Abstract: The concept advanced by Berridge and colleagues that intracellular Ca 2+ -stores can be mobilized in an agonist-dependent and messenger (IP 3 )-mediated manner has put Ca 2+ -mobilization at the center stage of signal transduction mechanisms. During the late 1980s, we showed that Ca 2+ -stores can be mobilized by two other messengers unrelated to inositol trisphosphate (IP 3 ) and identified them as cyclic ADP-ribose (cADPR), a novel cyclic nucleotide from NAD, and nicotinic acid adenine dinucleotide phosphate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 160 publications
1
52
0
Order By: Relevance
“…Production of intracellular ADPR is due to the enhanced NAD ϩ -glycohydrolase activity of CD38 in the presence of an increased concentration of its substrate NAD ϩ . Although CD38 is an ectoenzyme, with the active site facing the extracellular environment (59,60), its expression/activation in cells leads to the intracellular accumulation of cADPR, the product of its ADP-ribosyl cyclase activity (20,(61)(62)(63), and of ADPR, the product of its NAD ϩ -glycohydrolase activity (16,45).…”
Section: Discussionmentioning
confidence: 99%
“…Production of intracellular ADPR is due to the enhanced NAD ϩ -glycohydrolase activity of CD38 in the presence of an increased concentration of its substrate NAD ϩ . Although CD38 is an ectoenzyme, with the active site facing the extracellular environment (59,60), its expression/activation in cells leads to the intracellular accumulation of cADPR, the product of its ADP-ribosyl cyclase activity (20,(61)(62)(63), and of ADPR, the product of its NAD ϩ -glycohydrolase activity (16,45).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple defects are detected in the knock-out mice, including impairment in insulin secretion (85), increased susceptibil- ity to bacterial infection (84) 11). It is also noteworthy that the ubiquitous "NADase" activity observed in tissues that had no known function is greatly depressed after CD38 ablation (84), clarifying a long-time enigma.…”
Section: Physiological Functions Of Cd38mentioning
confidence: 99%
“…However, if the catalytic domain of CD38 is phosphorylated by protein kinase A (PKA), this domain should be in the cytosol to directly cyclize NAD, thereby synthesizing cAD-PR intracellularly. This suggests that although CD38 is believed to be a type-Ⅱ protein, at least a portion of the total CD38 is expressed as a type-Ⅲ membrane protein with its C-terminal catalytic domain sitting in the cyto-sol [53] . Since the number of positive charges that determine the polarity of membrane protein is equal on each side of the CD38 transmembrane segment, studies from protease digestion [54] and electron microscopy [55] showed that the nuclear CD38 might be a type-Ⅲ membrane protein.…”
Section: Topology Of Cd38mentioning
confidence: 99%